A treatable early onset epileptic encephalopathy: pyridoxamine 5’-phosphate oxidase deficiency - Dudipala, Sai C.; Potharajula, Sagar; Pabbathi, Srikanth R.; Battu, Krishna Chaithanya (International Journal of Contemporary Pediatrics, 2024)
Pyridox (am) ine 5’-phosphate oxidase (PNPO) deficiency is a rare epileptic encephalopathy condition due to mutations in PNPO gene. It is one of treatable metabolic epilepsies. It is unresponsive to antiseizure medications, but respond to pyridoxal-5-phosphate (PLP), active form of vitamin B6. It is characterized by refractory seizures from newborn or in utero, developmental delay. Based on refractory seizures, age of onset, negative biochemical profile and response to PLP, suspect PNPO deficiency. Next generation sequencing will help in the diagnosis. Early diagnosis and early initiation of PLP will help to cessation of seizures and better neurological outcome. Here we present a case of PNPO deficiency, which is diagnosed early and noticed good response with PLP.